Perilaku Konsumen Pada Produk Halal untuk Membangun Halal Lifestyle - Irvan Dian Dudiarto (International Consortium of Islamic Researchers (ICONIRs) CV. Branded Tech Indonesia, 2024)
AbstractConsumer behavior towards halal products plays a crucial role in shaping a halal lifestyle, particularly in countries with a significant Muslim population. This study examines the factors influencing consumer behavior in adopting halal products and their impact on the development of a halal lifestyle. Using a qualitative approach, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that religious awareness, product certification, and social influence significantly affect consumer preferences for halal products. Moreover, branding strategies and government policies play a vital role in promoting halal consumption. The study highlights that a strong halal lifestyle is supported by a comprehensive ecosystem involving businesses, regulators, and communities. Therefore, strengthening halal awareness through education, marketing, and regulatory reinforcement is essential to ensure the sustainability of the halal industry. Keywords: Consumer behavior, halal products, halal lifestyle, religious awareness, halal certification, consumer trust, business sustainability.